The relationship between organizational communication climate, supervisor communication climate and job satisfaction - Taştepe, Semra (My University, 2005)
The purpose of this research is to investigate the relationship between organizational communication climate, supervisor communication climate and job satisfaction. The data was gathered from the 198 workers in two production firms; both are national companies and belong to the same corporation. The first company has been carrying out TQM as a management philosophy and took out Tusiad Kalder Quality Award. This award is given only to the companies which applied the TQM in its all process and managerial dimensions successfully. On the other hand, the other company has been in the initial stages of TQM. There is no systematic and planned effort in line with the TQM requirements. The analysis yielded the following main results: 1. There is a significant relationship between the supervisor communication climate and job satisfaction. 2. There is a significant relationship between organizational communication climate and job satisfaction. 3. There is a significant difference between company that applies TQM and the company that doesn’t apply TQM in terms of supervisor communication climate. 4. There is a significant difference between company that applies TQM and the company that doesn’t apply TQM in terms of organizational communication climate. Results supported this hypothesis. 5. In terms of demographic characteristics of research data, there is no significant difference in job satisfaction according to status, gender and age

Bu çalışmanın temel amacı örgütsel iletişim iklimi, yönetici iletişim iklimi ve iş tatmini arasındaki ilişkiyi araştırmaya yöneliktir. Üretim sektöründen aynı holdinge ait olan iki firmada 198 çalışan üzerinde yapılan araştırmada , veri toplama yönetimi olarak anket kullanıldı. Firmalardan birisi Toplam kalite yönetimini bütün süreç ve yönetimsel boyutlarında bir yönetim biçimi olarak uygulamaktadır ve bu firma Tüsiad Kalder Kalite ödülünü almıştır. Bu ödül, Toplam Kalite Yönetimini bütün süreç ve yönetimsel boyutlarında başarı ile uygulayan firmalara verilmektedir. Diğer firma ise Toplam Kalite Yönetimi uygulaması açısından henüz başlangıç aşamasındadır ve henüz sistematik ve planlı uygulamaları yoktur. Araştırmanın genel sonuçları şunlardır: 1. Yönetici iletişim iklimi ve iş tatmini arasında anlamlı bir ilişki bulunmuştur. 2. Örgütsel iletişim iklimi ve iş tatmini arasında anlamlı bir ilişki vardır. 3. Yönetici iletişim iklimine göre yapılan karşılaştırmada, toplam kalite yönetimi uygulayan firma da empati, eşitlik ve esneklik boyutları anlamlı derecede farklı bulunmuştur.. 4. Örgütsel iletişim iklimine gore yapılan karşılaştırmada toplam kalite yönetimi uygulayan firma ve uygulamayan firma arasında anlamlı derecede fark bulunmuştur. 5. Demografik değişkenlere gore yapılan karşılaştırmalarda statü, yaş ve cinsiyete göre iş tatmininde bir farklılık bulunmamıştır.
Keywords: Genel yönetim; Örgütsel Davranış; Örgütsel İletişim; Personel yönetimi